AN ASSESSMENT OF FEDERAL GOVERNMENT HOUSING POLICIES AND PROGRAMMES IN OYO STATE NIGERIA (1986)
The urban housing problems in Oyo State have become very diverse and grievous in the recent time. The urban Population growth rate does not match the rate at which the housing units were being produced to accommodate the Population. However, the purpose of the work is to assess the policies and programmes that were meant to alleviate the Problems of housing shortage in particular. Housing policies and programmes of the Federal Government since the colonial period through the first to the current National Development Plan periods were identified and described. The policy of the colonial administration was to provide accommodation for their officials at the Regional Capital. In the first two plan periods, housing was lumped up with Urban and Regional Planning. In the Third and Fourth Plan periods it was recognised as a separate sector. There were policies to plan the physical layout of the buildings, ensuring environmental sanitation, providing shelter for all categories of individuals, encouraging availability of land, building Materials and building technology, financing housing programmes through loans, and providing infrastructural facilities to go along with housing. To implement the policies and programmes, the institutional framework involved were Federal Ministry of Housing and Environment, Federal Housing Authority (FHA) and the Federal Mortgage Bank. Five research questions were examined. Questionnaire was used to collect primary data. A kind of survey was carried out to the housing estates, and literature were contacted. Simple Statistical techniques of tabulation, percentages, correlation and regression analyses were used. Cartographic techniques were also used to present some Information. Some remarkable achievements were made. However, the analyses Show that the shortcomings surpassed the achievements. The colonial administration did not plan for any other city or town than the State Capital. Even after independence, the first two plan periods had policies and programmes for the state Capital alone. In the Third and Fourth Plan periods, there were policies for some selected urban centres but still with highest concentration at the State Capital. All institutions involved with the housing loan and housing delivery Systems were also found located at Ibadan. The low-cost housing units were concentrated at Ibadan while the rest were found scattered among the Local Government Head- quarters in the state. The housing units were found to be too costly and sophisticated for the category of people they were meant. The units were not located to replace any of the slums. They were haphazardly located at the outskirt of the cities and towns and thus cut-off from urban facilities and Services. The land use decree was not effective therefore lands for building houses were still very scarce. The Federal Mortgage Bank loan was restrictive and inaccessible. The public found the policies and programmes to be generally unsuitable and ineffective vis-a-vis the purpose. These shortcomings arise because the public were not made to participate at any stage of the policy formulation and implementation. Secondly, there were no data on housing conditions and housing industries. Lastly, the culture and norms of the societies for whom the policies and programmes were meant were never taken into consideration. Thus, the schemes excluded the truly urban majority. In conclusion, the work suggested what should be located where, and warned that the need to identify who- needs-what over space and time would be very crucial. Data Bank and Statistical Systems for House and housing industry were suggested. New questions were raised.